La dispersión de centros educativos, y la inadecuada preparación de los docentes dificultan el aprendizaje de los niños en zonas en rurales del Perú - Loconi Guerra, Liliana (2010)
As it is known, Peru is a country with great educational deficiencies and many of these deficiencies are easily evidenced in rural areas where children live a reality that is very different and distant from our own urban reality. Little is known about the critica! reality of rural education which has for main victims the children who expect to have the adequate means to be able to develop socially and personally, but instead they only find obstacles to accomplish an education.